2013
DOI: 10.1073/pnas.1307478110
|View full text |Cite
|
Sign up to set email alerts
|

Regulated ADAM17-dependent EGF family ligand release by substrate-selecting signaling pathways

Abstract: Ectodomain cleavage of cell-surface proteins by A disintegrin and metalloproteinases (ADAMs) is highly regulated, and its dysregulation has been linked to many diseases. ADAM10 and ADAM17 cleave most disease-relevant substrates. Broad-spectrum metalloprotease inhibitors have failed clinically, and targeting the cleavage of a specific substrate has remained impossible. It is therefore necessary to identify signaling intermediates that determine substrate specificity of cleavage. We show here that phorbol ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 49 publications
7
98
0
Order By: Relevance
“…In contrast, ADAM-17 knockdown did not show an effect on basal cell motility (Fig. 4F), possibly due in part to previously reported adhesion-related protein functions (23)(24)(25). Notably, however, ADAM-17 activity (as inferred using PrAMA) did not significantly correlate with cell motility in a positive manner in the CSR dataset, and ADAM-17 IP+activity results significantly anticorrelated with features of cell migration.…”
Section: Egfr Autocrine Signaling Regulates Adam-10 and -17 Catalyticsupporting
(Expert classified)
“…In contrast, ADAM-17 knockdown did not show an effect on basal cell motility (Fig. 4F), possibly due in part to previously reported adhesion-related protein functions (23)(24)(25). Notably, however, ADAM-17 activity (as inferred using PrAMA) did not significantly correlate with cell motility in a positive manner in the CSR dataset, and ADAM-17 IP+activity results significantly anticorrelated with features of cell migration.…”
Section: Egfr Autocrine Signaling Regulates Adam-10 and -17 Catalyticsupporting
(Expert classified)
“…To clarify the molecular mechanisms underlying the α-cyperone effects on EPCR shedding induced by 2 µM PMA, we first tested the protein, mRNA level and activity of TACE in HUVECs. TACE has been reported to mediate a number of protein cleavage events, [9][10][11][12][13] including EPCR 8) and its function mainly depends on its activity and protein expression, which we found could be inhibited by α-cyperone. It is well known that TACE is regulated by MAPK signaling which has been reported that ERK and p38 could activate TACE, 33,34) so we measured the effect of α-cyperone on the phosphorylation of MAPK induced by PMA.…”
Section: Discussionmentioning
confidence: 58%
“…α-Cyperone Inhibits PKC Activation Induced by PMA A series of experiments showed that TACE is also regulated by the PKC pathway [9][10][11][12][13] ; furthermore, PMA is also a potent PKC activator. All of these reports indicate that the activation of the PKC pathway is involved in EPCR shedding, but which PKC isoform is playing the pivotal role in this process is still unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that ectodomain cleavage requires tight regulation. How ectodomain cleavage is regulated and made substrate specific is largely unknown to date.The metalloproteases ADAM10 and ADAM17 are involved in the cleavage of most substrates that undergo regulated cleavage induced by intracellular signaling pathways, which are, in turn, activated by G protein-coupled receptors (GPCRs) or RTKs (2) involving the activation of protein kinase C (PKC) isoforms (5,28,29). An obvious way to regulate cleavage is modulation of the availability and activity of the enzymes.…”
mentioning
confidence: 99%